Towards a neo-Polanyian approach to money: integrating the concept of debt - Saiag, Hadrien (Economy & Society, 2014)
This paper aims to reconsider Polanyi's approach to money. His best-known writing on money uses is deeply original and presents strong insights that dissociate money from the concept of the market. Polanyi also developed an interesting non-dichotomous understanding of money in hisThe great transformation. However, taken together, these two contributions lead to some unresolved questions: his critique of the orthodox approach to money is ambivalent; his argument to separate payment from account is weak; and, most important, he ultimately makes an incomplete break with the classical real/monetary dichotomy. This paper proposes a distinction between money as a set of instruments and practices and money as a concept, through the integration of John Commons's concept of debt into Polanyi's framework. This reformulation allows us to resolve Polanyi's unresolved questions while preserving his major contributions, and leads to a more complex understanding of money.
Economics; Anthropology
Keywords: COMMONS; J.R.; COMMONS; John; Great Transformation; The (Book); debt; debt management; economic anthropology; economic aspects; economics; money plurality; political aspects; theories of money

The Anthropology of Money and Finance: Between Ethnography and World History - Hart, Keith; Ortiz, Horacio (Annual Review of Anthropology, 2014)
We review here recent developments in the anthropology of money and finance, listing its achievements, shortcomings, and prospects, while referring back to the discipline's founders a century ago. We take our departure from the work of Marcel Mauss and Karl Polanyi, both of whom combined openness to ethnographic research with a vision of world history as a whole. Since the 1960s, anthropologists have tended to restrict themselves to niche fields and marginal debates. The anthropological study of money and ethnographies of finance, in particular, have been the focus of much research since the 1980s. Despite taking on new objects and directions, anthropologists still find it difficult to connect their situated analyses with global processes and world history. We propose some conceptual and empirical directions for research that would seek to overcome these limitations by integrating ethnography more closely with human history, while stressing the importance of money in shaping world society and attempts to reform it.
Anthropology
Keywords: MAUSS; Marcel; 1872-1950; distribution; economic anthropology; ethnology; exchange; finance; globalization; history; money; politics; world society

The Double Movement of Immovable Property Rights in Papua New Guinea - Filer, Colin (Journal of Pacific History, 2014)
Papua New Guinea (PNG) is one of many countries around the world where the relationship between customary land tenure and economic development has been hotly debated for a long time. A commonplace of the debate in PNG is that 97% of the nation's land is held under customary tenure, while only 3% has been alienated, and these proportions have not changed since the country became independent in 1975. This paper shows that the boundary between customary and alienated forms of land or immovable property was already showing signs of instability in the late colonial period, and this instability has been greatly magnified in the post-colonial period. The areas of land subject to some form of partial alienation have increased along with the ways and means by which immovable property has been ‘mobilised’, while a variety of customary claims to previously alienated areas have grown stronger over the same period. Although Karl Polanyi's idea of a ‘double movement’ can throw some light on this phenomenon, the PNG case also reveals a new side to the application of this concept.
History; Anthropology
Keywords: Papua New Guinea; agriculture; forestry; forests and forestry; land tenure; mineral industries; mining; politics and government; property rights

Three Shades of Embeddedness, State Capitalism as the Informal Economy, Emic Notions of the Anti-Market, and Counterfeit Garments in the Mauritian Export Processing Zone - Neveling, Patrick (Research in Economic Anthropology, 2014)
Purpose – This paper furthers the analysis of patterns regulating capi-talist accumulation based on a historical anthropology of economic activ-ities revolving around and within the Mauritian Export Processing Zone (EPZ). Design/methodology/approach – This paper uses fieldwork in Mauritius to interrogate and critique two important concepts in contemporary social theory – "embeddedness" and "the informal economy." These are viewed in the wider frame of social anthropology's engagement with (neoliberal) capitalism. Findings – A process-oriented revision of Polanyi's work on embedded-ness and the "double movement" is proposed to help us situate EPZs within ongoing power struggles found throughout the history of capital-ism. This helps us to challenge the notion of economic informality as supplied by Hart and others. Social implications – Scholars and policymakers have tended to see eco-nomic informality as a force from below, able to disrupt the legal-rational nature of capitalism as practiced from on high. Similarly, there is a view that a precapitalist embeddedness, a "human economy," has many good things to offer. However, this paper shows that the practices of the state and multinational capitalism, in EPZs and elsewhere, exactly match the practices that are envisioned as the cure to the pitfalls of capitalism. Value of the paper – Setting aside the formal-informal distinction in favor of a process-oriented analysis of embeddedness allows us better to understand the shifting struggles among the state, capital, and labor.
Anthropology
Keywords: Mauritius; capitalism; economic anthropology; embeddedness; embeddedness (socioeconomic theory); ethnohistory; export processing zones; informal sector (economics); neoliberalism